2021
DOI: 10.1097/med.0000000000000639
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disruptions and bone health: what do we know so far?

Abstract: Purpose of review This review briefly summarizes the growing body of literature addressing the skeletal consequences of sleep and circadian disruption. Recent findings The most recent data in the field suggest that the diurnal variation in bone turnover markers are because of endogenous circadian rhythmicity linked to clock genes in all bone cells; in a small human intervention study, cumulative sleep restriction with concurrent circadian disruption neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…The mechanisms underlying the association of sleep traits with incidental fractures are still unknown. Previous studies have suggested that impaired cognitive function or depression, falls, decreased muscle strength, bone mineral density (BMD), and comorbidities may mediate this association [ 11 , 31 , 33 , 45 , 46 ]. For example, short/long sleep duration was frequently comorbid with falls, osteoporosis, pain, mental disorders, and obstructive sleep apnea [ 45 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the association of sleep traits with incidental fractures are still unknown. Previous studies have suggested that impaired cognitive function or depression, falls, decreased muscle strength, bone mineral density (BMD), and comorbidities may mediate this association [ 11 , 31 , 33 , 45 , 46 ]. For example, short/long sleep duration was frequently comorbid with falls, osteoporosis, pain, mental disorders, and obstructive sleep apnea [ 45 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, sleep in uences bone metabolism by in uencing the rhythmicity of bone cells, sympathetic tone, in ammation, metabolic balance, and physical activity. Sleep duration is closely associated with the circadian rhythm, as evident from the internal rhythm in bone turnover markers and the presence of clock genes within bone cells [23][24][25]. Animal models with the knockout of clock genes indicate the importance of the circadian rhythm in maintaining optimal skeletal health.…”
Section: Potential Mechanisms Between Short Sleep Duration and Osteop...mentioning
confidence: 99%
“…Animal models with the knockout of clock genes indicate the importance of the circadian rhythm in maintaining optimal skeletal health. Disruptions in sleep or circadian rhythms may therefore adversely affect bone health [24].…”
Section: Potential Mechanisms Between Short Sleep Duration and Osteop...mentioning
confidence: 99%
“…However, alerts from these devices, hypoglycemia and hyperglycemia are known to disrupt sleep in people with T1D. Swanson [8] reviewed recent publications demonstrating that sleep disruptions may be associated with low bone formation and increased fracture risk. In that issue, two reviews were dedicated on highlighting chronic hyperglycemia leading to increased advanced glycation endproducts (AGEs) accumulation and its possible implication on tissue material properties and skeletal fragility in people with diabetes [9,10].…”
mentioning
confidence: 99%